Rain Culture: Rain Induced Behavioral Changes of People Moving on the Streets in Central Ho Chi Minh City - Luu, Tuan Anh (Journal of Urban Culture Research, 2021)
Rain is a natural phenomenon that has existed for a long time in people’s lives, greatly affecting the lifestyle of people and the appearance of Ho Chi Minh City. All the methods, concepts, behaviors and relationships of people in Ho Chi Minh City in their interaction with rain form the whole of the so-called rain induced behavioral culture. Studying the rain induced behavioral changes of people moving on the streets in central Ho Chi Minh City is a meaningful case study to identify the overall picture of behavioral culture with rain in particular, with weather in general, of people in Ho Chi Minh City. This paper suggests the direction of extensive or in-depth research on the relationship between people and nature in Ho Chi Minh City from cultural view as one of the approaches that are not alien to people’s lives but rather new to social science research.